2017
DOI: 10.1016/j.celrep.2017.10.057
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of the Apelinergic Axis Accelerates Aging, whereas Its Systemic Restoration Improves the Mammalian Healthspan

Abstract: SUMMARY Aging drives the occurrence of numerous diseases, including cardiovascular disease (CVD). Recent studies indicate that blood from young mice reduces age-associated pathologies. However, the “anti-aging” factors in juvenile circulation remain poorly identified. Here, we characterize the role of the apelinergic axis in mammalian aging and identify apelin as an anti-aging factor. The expression of apelin (apln) and its receptor (aplnr) exhibits an age-dependent decline in multiple organs. Reduced apln sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 42 publications
1
49
1
Order By: Relevance
“…Another important circulatory factor affecting satellite cell function in sarcopenic muscles is the exercise‐induced myokine apelin . Apelin levels decrease with age, and studies in mice show that this has important consequences for healthspan . A recent study revealed an association between apelin signaling and the beneficial effects of exercise, and also identified a positive effect on the regenerative capacity of aged muscle stem cells .…”
Section: How Muscle Stem Cells Agementioning
confidence: 99%
“…Another important circulatory factor affecting satellite cell function in sarcopenic muscles is the exercise‐induced myokine apelin . Apelin levels decrease with age, and studies in mice show that this has important consequences for healthspan . A recent study revealed an association between apelin signaling and the beneficial effects of exercise, and also identified a positive effect on the regenerative capacity of aged muscle stem cells .…”
Section: How Muscle Stem Cells Agementioning
confidence: 99%
“…For instance, ageing is known to be associated with both EC and CM dysfunction, resulting in heart hypertrophy and stiffness. During ageing, expression of both APLN and its APJ receptor are decreased and APLN infusion in 15-month-old mice reduces cardiac hypertrophy (Rai et al 2017). On the other hand, ET-1 increases in aged hearts, although its pathogenic role in determining cardiac stiffness seems to be related to its effect on cardiac fibroblasts rather than CMs (Wang et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Apelin signaling down‐regulation is correlated with age‐related diseases and accelerates them. Administration of apelin can ameliorate these disorders (Rai et al, ). Oxidative stress can lead to aging‐associated diseases (Liguori et al, ).…”
Section: Apelin and The Apj (Apelin Receptor Putative Receptor Protementioning
confidence: 99%
“…Oxidative stress can lead to aging‐associated diseases (Liguori et al, ). Apelin raises the activity of antioxidant enzymes (Than et al, ), indicating this peptide acts as an anti‐aging factor (Rai et al, ). Apelin also decreases the reactive oxygen species (ROS) generation and pro‐oxidant enzyme expression in adipocytes, regulates glucose metabolism, and improves insulin resistance.…”
Section: Apelin and The Apj (Apelin Receptor Putative Receptor Protementioning
confidence: 99%